2019
DOI: 10.1111/tid.13174
|View full text |Cite
|
Sign up to set email alerts
|

Successful optimization of antiretroviral regimens in treatment‐experienced people living with HIV undergoing liver transplantation

Abstract: Modern antiretroviral therapy (ART) extends life expectancy for people living with HIV (PLWH). However, most older PLWH (≥50 years) “aged” with HIV and were exposed to historical HIV care practices and older, more toxic ART. In PLWH with exposure to older and multiple ART regimens, the drug interactions between ART frequently used in treatment‐experienced persons and commonly used immunosuppressants remain a significant challenge. However, the advent of newer ART classes (eg, integrase non‐strand transfer inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Small case reports evaluating the use of raltegravir have found that it is generally well tolerated and effective to use in the setting of LT with minimal side effects [ 88 90 ]. Due to its high barrier to resistance and its once-a-day dosing, dolutegravir is the favored INSTI [ 84 , 91 ].…”
Section: Clinical Management Issues In Liver Transplant Candidates An...mentioning
confidence: 99%
“…Small case reports evaluating the use of raltegravir have found that it is generally well tolerated and effective to use in the setting of LT with minimal side effects [ 88 90 ]. Due to its high barrier to resistance and its once-a-day dosing, dolutegravir is the favored INSTI [ 84 , 91 ].…”
Section: Clinical Management Issues In Liver Transplant Candidates An...mentioning
confidence: 99%
“…Switching to ARVs with less DDI potential is recommended [49]. If boosted or enzyme inducing ARVs are necessary, close monitoring of immunosuppressant concentrations with careful dose titration is recommended [50].…”
Section: Drug Interactions Leading To Adverse Eventsmentioning
confidence: 99%